2012
DOI: 10.1128/mcb.06546-11
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans Dosage Compensation Regulates Histone H4 Chromatin State on X Chromosomes

Abstract: Dosage compensation equalizes X-linked gene expression between the sexes. This process is achieved in Caenorhabditis elegans by hermaphrodite-specific, dosage compensation complex (DCC)-mediated, 2-fold X chromosome downregulation. How the DCC downregulates gene expression is not known. By analyzing the distribution of histone modifications in nuclei using quantitative fluorescence microscopy, we found that H4K16 acetylation (H4K16ac) is underrepresented and H4K20 monomethylation (H4K20me1) is enriched on herm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
142
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(150 citation statements)
references
References 83 publications
(108 reference statements)
5
142
2
1
Order By: Relevance
“…Triplicate analyses of set-1 and set-4 RNAi were consistent (supplementary material Table S7). sir-2.1, which has been reported to act to deacetylate lysine 16 of H4 (H4K16Ac) downstream of the DCC (Wells et al, 2012), also modestly suppressed developmental delay in rict-1 mutants ( Fig. 6C; supplementary material Table S7).…”
Section: Dpy-21mentioning
confidence: 98%
See 3 more Smart Citations
“…Triplicate analyses of set-1 and set-4 RNAi were consistent (supplementary material Table S7). sir-2.1, which has been reported to act to deacetylate lysine 16 of H4 (H4K16Ac) downstream of the DCC (Wells et al, 2012), also modestly suppressed developmental delay in rict-1 mutants ( Fig. 6C; supplementary material Table S7).…”
Section: Dpy-21mentioning
confidence: 98%
“…SET-4 activity, which di-and trimethylates H4K20, is correspondingly decreased during embryonic dosage compensation (Vielle et al, 2012), but SET-4 has been reported to mediate some of the effects of the DCC (Wells et al, 2012). H4K20me1 likely contributes to the chromosomal condensation Rice et al, 2002), restricting expression of X chromosomal genes during dosage compensation.…”
Section: Dpy-21mentioning
confidence: 99%
See 2 more Smart Citations
“…16 At the chromatin level, the dosage compensated X chromosomes are depleted for the histone variant H2A.Z (HTZ-1) and H4K16 acetylation while they carry high H4K20 monomethylation. [17][18][19][20] The first two might be a consequence of lower transcription levels, while the latter is a consequence of DCC binding as the methylation mark spreads with the DCC. 18 The function of this methylation marks remains however elusive.…”
Section: Introductionmentioning
confidence: 99%